Theme-centered interaction and developmental tasks as research method and pedagogical tool regarding identity development in VET - Thole, Christiane (Frontiers in Psychology, 2023)
This paper presents the methodology of a PhD project on identity development in German dual track VET. The mixed methods approach comprises theory-driven longitudinal case studies using qualitative and quantitative data and a document analysis of curricula. The study was part of a larger design-based research project and aimed to evaluate a newly developed and implemented VET curriculum for the retail sector from the learners’ point of view. The new curriculum contained a special competence dimension to foster vocational identity development and a major interest was to investigate the extent to which the curriculum succeeded to do so. The paper will start with a summary and assessment of limitations and advantages of research designs applied in different existing studies examining identity development. The author will then outline identity-relevant theories and approaches that proved to be useful for her research interest. Subsequently, she will describe the resulting design for collecting and analyzing her data. The core result consists of a theme-centered process analysis visualizing the individual state of developmental tasks. With the presentation of three exemplary cases she will illustrate how her approach allowed her to deeply understand the identity of the respective person and at the same time generate general insights about identity development of learners in VET. Finally, strengths and limitations of her approach will be discussed. This research approach is also suited to supporting pedagogical design, representing major added value.